(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the optimum surgical technique for inguinal hernia repair, Shouldice or Bassini’s ? Study : Retrospective comparative study. Place and Durationof Study: This study was conducted between 2004 to 2006 in the surgical ward DHQ Hospital Karak. 200 patients with unilateral & primary inguinal hernia were randomly allotted to either Shouldice or BasDesignsini’s repair. The cases were collected either as emergencies or electively. Materials and Methods: All the patients had primary and unilateral inguinal hernia. They were operated electilively or as emergencies. Patients were randomly allotted to either Shouldice or Bassini’s repair. The Shouldice was performed with 2/0 prolene in four layers while the bassini’s repair was done with prolene 0 or 1. Results: The patients operated for inguinal hernia were followed for up to 5 years. The shouldice repair was found associated with a lowest recurrence rate of 3% and the Bassini’s repair with 5.7%. The difference remains statistically significant (P<0.001). Conclusion: The Shouldice repair for inguinal hernia was associated with a recurrence rate of less than 1% in the Shouldice clinic at TORONTO. Here in this study the Shouldice resulted in 3% recurrence rate which is nearer to the international value while the Bassini’s repair was associated with a recurrence rate of 5.7% which is higher than the Shouldice repair. The Shouldice repair for inguinal hernia should be the Gold Standard and serves as the basis for comparison for all other techniques, be they prosthetic or laparoscopic